2022
DOI: 10.1093/europace/euac053.276
|View full text |Cite
|
Sign up to set email alerts
|

Visualizable vs. standard, non-visualizable steerable sheath for pulmonary vein isolation procedures: randomized, single-center trial

Abstract: Funding Acknowledgements Type of funding sources: None. Background/Introduction Steerable sheaths are frequently used to improve catheter contact during pulmonary vein isolation (PVI) procedures. A new type of visualized (by electroanatomical mapping system) steerable sheath has become available in clinical treatment. Purpose We aimed to compare procedural da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Results from the current study are consistent with previous reports showing that the VIZIGO visualizable steerable sheath had similar safety to the Agilis non-visualizable sheath, 16 with shorter fluoroscopy times and lower fluoroscopy doses in patients undergoing PVI for the treatment of AF. 15 , 20 As was reported here, overall procedure time was similar between the visualizable and non-visualizable sheath groups in previous studies. 15 , 20 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results from the current study are consistent with previous reports showing that the VIZIGO visualizable steerable sheath had similar safety to the Agilis non-visualizable sheath, 16 with shorter fluoroscopy times and lower fluoroscopy doses in patients undergoing PVI for the treatment of AF. 15 , 20 As was reported here, overall procedure time was similar between the visualizable and non-visualizable sheath groups in previous studies. 15 , 20 …”
Section: Discussionsupporting
confidence: 86%
“… 15 , 20 As was reported here, overall procedure time was similar between the visualizable and non-visualizable sheath groups in previous studies. 15 , 20 …”
Section: Discussionsupporting
confidence: 86%
“…Numerous studies have confirmed the feasibility of near-zero and zero-fluoroscopy approaches for CTI ablation, including their successful application as an extension to pulmonary vein isolation procedures within a single session (5,(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the advent of visualizable steerable sheaths has yielded significant advancements in mitigating radiation exposure during catheter ablation procedures (24).…”
Section: Discussionmentioning
confidence: 99%